RNA Motifs and Modification Involve in RNA Long-Distance Transport in Plants - Wang, Tao; Li, Xiaojun; Zhang, Xiaojing; Wang, Qing; Liu, Wenqian; Lu, Xiaohong; Gao, Shunli; Liu, Zixi; Liu, Mengshuang; Gao, Lihong; Zhang, Wenna (Frontiers in Cell and Developmental Biology, 2021)
A large number of RNA molecules have been found in the phloem of higher plants, and they can be transported to distant organelles through the phloem. RNA signals to evolve fortification strategies by long distance transportation when suffering from various physiological challenges. However, the mechanism of RNA selectively transportation through phloem cells is still in progress. First, RNA motifs including Polypyrimidine (poly-CU) sequence, tRNA-related sequence, Single Nucleotide Polymorphism (SNP) bound with specific RNA binding proteins to form Ribonucleotide protein (RNP) complexes, then facilitating RNA mobility in plants. Furthermore, some RNA secondary structure such as tRNA-like structure (TLS), untranslation region (UTR) of mRNA, stem-loop structure of pre-miRNA also contributed to the mobility efficiency of RNAs in plant. The latest researchers found that RNA methylation such as methylated 5’ cytosine (m5C) played an important role in RNA transport and function. These studies lay a theoretical foundation to uncover the mechanism of RNA transport. The importance of this review is not only to explore the mechanism of RNA signaling, but also to provide an insight for plant growth, development and stress resistance regulation in RNA levels.